Defects/vacancies engineering and ferromagnetic behavior in pure ZnO and ZnO doped with Co nanoparticles. (November 2016) - Aljawf, Rezq Naji; Rahman, F.; Kumar, Shalendra
Graphical abstract: Highlights: ⿢ Undoped and Co doped ZnO NPs were synthesized through auto-combustion route. ⿢ Energy deep-levels created by defects in the band gap region have been studied. ⿢ Electronic structure at Fermi level and VBM has been studied by using XPS. ⿢ The contribution of native defects on the FM of Co-ZnO NPS has been studied. ⿢ A strong correlation between the d 0 ferromagnetism in ZnO NPs and native defects. Abstract: Nanoparticles (NPs) of undoped and Co (10%) doped ZnO were synthesized through auto-combustion route. XRD patterns confirm the single phase nature and the incorporation of Co 2+ ions into ZnO matrix. The average crystallite sizes were ⿼22.1 and ⿼14.6 nm for undoped and Co doped ZnO respectively. Native defects/vacancies create energy deep-levels (EDLs) in the band gap region that have been studied through photoluminescence (PL) spectroscopic. The donor band nature of Vo is ⿼0.79 eV above valance band maximum (VBM). VBM and electronic structure have been evaluated via X-ray photoelectron spectroscopy (XPS). Undoped and Co doped ZnO NPs show ferromagnetic (FM) behavior. The weak FM in Co doped ZnO can be elucidated by bound magnetic polarons (BMPs) mechanism. Zinc vacancies (VZn ) seem to be the responsible for d 0 ferromagnetism in pure ZnO NPs. We aim to correlate the FM ordering with the native defects concentrated at the surface of NPs.